Development of Disaster Mitigation Learning Media for Individuals with Intellectual Disabilities - Mohamad Defrizal Fadhlan; Alwin Alwin (University of Muhammadiyah Malang, 2026)
Background: People with disabilities are vulnerable to natural disasters primarily due to their marginalization, lack of disaster preparedness knowledge, and the absence of adequate evacuation facilities during emergencies also the lack of disability-friendly educational media on disaster mitigation results in their inadequate preparedness to face disasters. Objectives: This study aims to develop a disaster mitigation learning application that can help people with intellectual disabilities in learning about disaster mitigation. Methods: The application named Edubencana developed using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model and built with React Native Framework. Content validity is conducted to assess the suitability of the content within the application. The data obtained is calculated using the Aiken v-index to assess the suitability of the application content. Subsequently, trials were conducted on students with intellectual disabilities twice utilizing a pre-test and post-test approach, where changes in their comprehension levels were then measured using Hake's normalized gain. Results: The developed media achieved a valid category with an Aiken’s V score of 0.72. The field trial revealed a significant improvement in students' learning outcomes, with the majority of students achieving a Normalized Gain score in the high category. Conclusions: The Edubencana application, featuring a simple interface and engaging visual illustrations, is highly effective and worthy of recommendation as an inclusive alternative learning medium to improve disaster mitigation competencies for students with intellectual disabilities.